Tahlīlu Muḥtawā Taʿlīmi al-Luġah al-ʿArabiyyah min Ḥilāli al-Mawqiʿ al-Iliktrūnī "Bayyinah Dream" wa Musāhamatihi fī Taʿlīmi al-Luġah al-ʿArabiyyah fī ʿAṣri al-Mujtamāʿ 5.0: Analysis of Arabic Language Teaching Content from the Website "Bayyinah Dream" and Its Contribution to Arabic Language Learning in the Era of Society 5.0 - Abicandra, Muhammad Nidom Hamami; Al Farouqi, Casilda (Critical Review of English-Arabic World Journal, 2024)
يوفر التعليم الحديث في عصر المجتمع 5.0 وصولاً واسعًا لجميع فئات المجتمع إلى المحتوى التعليمي. ومع ذلك، فإن توفير تجربة تعلم اللغة العربية في إطار مفهوم التعلم مدى الحياة، لفهم وتعمق تعاليم القرآن الكريم كدليل للحياة، ومصدر للمعرفة، ومرجع لتعاليم الإسلام، لم يتحقق بعد بالكامل ولم يشعر به جميع أفراد المجتمع. وجد الباحث أن محتوى تعليم اللغة العربية على موقع "Bayyinah Dream" يُعد مصدرًا بديلًا يمكن أن يلبي احتياجات المجتمع في تعلم اللغة العربية لأغراض محددة، مستفيدًا من مفهوم التعلم مدى الحياة، ومعززًا بالاستخدام الأمثل للتكنولوجيا في عملية التعلم. أما طريقة جمع البيانات فتمت باستخدام الملاحظة والتوثيق. يهدف هذا البحث إلى استكشاف محتوى تعليم اللغة العربية على موقع "Bayyinah Dream" كمصدر بديل لتلبية احتياجات المجتمع. تصف الدراسة هيكل البرنامج، والمواد، وطرق التدريس، وتقيّم مساهمته في تعليم اللغة العربية في مجتمع 5.0. وتُبرز النتائج الطبيعة الجاذبة للبرنامج، وتوافقه مع القرآن الكريم كدليل للحياة، والترتيب المنظم للمواد. ويسهّل المحتوى على موقع "Bayyinah Dream" تجربة تعلم ممتعة وطويلة الأمد. Modern education in the era of Society 5.0 provides broad access for all segments of society to educational content. However, providing a learning experience for the Arabic language within the concept of lifelong learning, to understand and delve into the teachings of the Quran as a guide for life, a source of knowledge, and a reference on the teachings of Islam, has not been fully realized and felt by all segments of society. The researcher found that the content of Arabic language education on the website "Bayyinah Dream" serves as an alternative source that can meet the community's needs for learning Arabic for specific purposes, utilizing the concept of lifelong learning and maximizing the use of technology in the learning process. As for the method of collecting his data using observation and documentation. This study aims to explore the Arabic language education content on the "Bayyinah Dream" website as an alternative source to meet community needs. The study describes the program structure, materials, teaching methods, and evaluates its contribution to Arabic language education in Society 5.0. The findings highlight the engaging nature of the program, its alignment with the Quran as a life guide, and the structured arrangement of materials. The content on "Bayyinah Dream" facilitates enjoyable and lifelong learning experiences.